Metodología para el Modelado Tridimensional de los Ligamentos de la Articulación Coxofemoral - Pérez Aguilar, Bruno; Herrera Paz, Sergio; Vidal Lesso, Agustín; Bayod López, Javier (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
The aim of this research is to propose a methodology to model the main ligaments of the hip joint by using computational modeling software such as CATIA® V5. This methodology is divided into two main parts. The first one concerns the conception of the ligaments. The second one refers to the assembly of the ligaments within a computational model of the bones of the pelvis and the femur. Once the ligament models were generated following the proposed methodology, dimensional values were measured to later compare them with those reported in several experimental investigations. In this sense, the percentage of error obtained between these values (up to 8.5 %) is a way of quantitatively validating the generated models, and therefore ensure that the geometry of each ligament can be used for future research that seeks to simulate and analyze the behavior of the ligaments under different physiological conditions.